Genetically Induced Cell Death in Bulge Stem Cells Reveals Their Redundancy for Hair and Epidermal Regeneration. (17th February 2015) - Driskell, Iwona; Oeztuerk-Winder, Feride; Humphreys, Peter; Frye, Michaela
Abstract: Adult mammalian epidermis contains multiple stem cell populations in which quiescent and more proliferative stem and progenitor populations coexist. However, the precise interrelation of these populations in homeostasis remains unclear. Here, we blocked the contribution of quiescent keratin 19 (K19)-expressing bulge stem cells to hair follicle formation through genetic ablation of the essential histone methyltransferase Setd8 that is required for the maintenance of adult skin. Deletion of Setd8 eliminated the contribution of bulge cells to hair follicle regeneration through inhibition of cell division and induction of cell death, but the growth and morphology of hair follicles were unaffected. Furthermore, ablation of Setd8 in the hair follicle bulge blocked the contribution of K19-postive stem cells to wounded epidermis, but the wound healing process was unaltered. Our data indicate that quiescent bulge stem cells are dispensable for hair follicle regeneration and epidermal injury in the short term and support the hypothesis that quiescent and cycling stem cell populations are equipotent. Stem Cells   2015;33:988–998